Clinical efficacy of intravesical electrical stimulation on detrusor underactivity: 8 Years of experience from a single center. Issue 38 (September 2017) - Deng, Han; Liao, Limin; Wu, Juan; Chen, Guoqing; Li, Xing; Wang, Zhaoxia; Wan, Li
Abstract : Abstract: The aim of this study was to retrospectively evaluate the effectiveness of intravesical electrical stimulation (IVES) on detrusor underactivity (DU). From 2009 to 2016, a total of 105 patients with symptoms of DU who were treated with IVES were included in this retrospective study. The medical records, physical examination findings, urine culture results, and video-urodynamic studies were reviewed. Changes in post-void residual urine (PVR) and voiding efficiency (VE) were included for evaluation of efficacy. Patients achieving a >50% reduction in the PVR were regarded as responders. A >80% reduction in the PVR was considered obvious improvement. A questionnaire was administered to patients with bladder sensation. Of the 105 patients, the information of residual urine volume and voiding volume was obtained in 89 patients, and detailed pre- and post-IVES bladder sensation information was available on 96 patients. Of the 89 patients, 47.2% (42/89) were responders and achieved a >50% reduction in the PVR. Obvious improvement in the PVR, defined as a >80% reduction, occurred in 27% (24/89) of the patients. VE developed in 76.4% (68/89) of the patients, and 30.3% (27/89) of the patients increased >50%. Significant improvements in the PVR and VE were observed during IVES treatment ( P  < .05). Based on the questionnaire, bladder sensation developed and was sustained in 44.8% (43/96) of the patients. IVES provides a promising method for improving the PVR and VE in a majority of patients with DU. Thus, IVES is worth to further study and carry out.